The Influence of Financial Performance, Dividend Policy, on Stock Prices with Tax Compliance Level as an Intervening Variable: Study of Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange in 2018 – 2023 - M. Imam Suswandoyo; Diana lestari; Purwanti; Sukiranto (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To determine the effect of Financial Performance, Dividend Policy, on Stock Prices with Tax Compliance Level as an intervening variable. Background Problems: The growth in the number of investors in 2020 was very significant compared to the previous year, which was dominated by millennials. Novelty: Testing the level of stock prices with the level of tax compliance as an intervening variable in the property sector. Research Methods: Using the object of the property and real estate sector companies for the period 2018-2023 listed on the IDX, with an analysis tool, namely SPSS on 11 companies with a sample of 66. Finding/Results: Financial Performance has a significant effect on Stock Prices, Dividend Policy has a significant effect on Stock Prices and Tax Compliance Level has an insignificant effect on Stock Prices, Financial Performance and Dividend Policy have a significant effect and the level of tax compliance is indirectly able to mediate the effect of financial performance on stock prices, and indirectly dividend policy through the level of tax compliance has a significant negative effect on Stock Prices. Conclusion: Companies should consider their dividend policy carefully, because this decision has a direct impact on the market value of the stock, investors may view dividends as an effective signal of the company's financial health and future prospects.